2019
DOI: 10.1016/j.dyepig.2018.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the electronic properties of the π-spacer of chromophores linked to calix[4]arene platform for DSSCs applications

Abstract: the electronic properties of the π-spacer of chromophores linked to calix[4]arene platform for DSSCs applications, Dyes and Pigments (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The enhancement of absorbance per chromophore unit had been observed in previous studies. For instance, a 2.4 increase factor was reported for double dyes with the alkyl linkage in the π-spacer, as Cx-2-TPA [20] compared with the single TPA [15]. In the present work, with dyes having the alkyl linkage in the donor-part, Cx-2-AT-L, the light absorption increase is even greater.…”
Section: Optical Propertiessupporting
confidence: 44%
See 2 more Smart Citations
“…The enhancement of absorbance per chromophore unit had been observed in previous studies. For instance, a 2.4 increase factor was reported for double dyes with the alkyl linkage in the π-spacer, as Cx-2-TPA [20] compared with the single TPA [15]. In the present work, with dyes having the alkyl linkage in the donor-part, Cx-2-AT-L, the light absorption increase is even greater.…”
Section: Optical Propertiessupporting
confidence: 44%
“…Nonetheless, it is noticeable the increase of the V oc in the devices prepared with Cx-2-AT-L; this result can be explained due tothe cone scaffold that could inhibit the dark current caused by the recombination of the TiO 2 conduction band electrons with I 3 -. [19,20,31,32] When dyes with different linkage location are compared, it is observed that the dye loading of the sensitizer with the alkyl linkage on the donor part, Cx-2-AT-L (1.92 10 -7 ),is slightly higher than the loading of dyes with the linkage on the π-spacer, Cx-2-TPA(1.30 10 -7 mol/cm 2 ). [19] Moreover, due to the absorption characteristics of these dyes, the IPCE spectrum of the device prepared with Cx-2-AT-L is broader than the one of Cx-2-TPA.…”
Section: Photovoltaic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] In our research group we have prepared sensitizers connected through a -linker and it has been proved that the introduction of several dyes in a scaffold allows increasing the distance between the chromophore groups avoiding their interaction [22] and, at the same time, the extinction coefficient is increased, allowing the device to work in conditions of low luminosity. [23,24] The goal of this paper is to study the properties of difunctionalized dyes based on a novel σ-linkage, the 3-methyl-1,1-cyclohexane, with two chromophores, which are constituted by N, N-dialkylaniline as donor (D), thiophene or bithiophene as -spacer () and a cyanoacetic group as acceptor (A) and anchoring group. The effect of this linkage on the physical properties and photovoltaic performances of these double dyes will be evaluated and compared with those of the corresponding single D--A structure.…”
Section: Introductionmentioning
confidence: 99%